Oyster reef restoration - aquaculture interactions: maximizing positive synergies - Bishop, Melanie J.; Lanham, Brendan S.; Esquivel-Muelbert, Juan R.; Cole, Victoria J.; Faelnar, Kristine M.; Jenkins, Charlotte; Keating, Jillian; Martínez-Baena, Francisco; O’Connor, Wayne A. (Frontiers in Marine Science, 2023)
Globally, oyster reef restoration is on the rise. In many instances, restoration is occurring alongside established oyster aquaculture industries that grew to prominence following oyster reef demise. This paper examines the potential positive and negative interactions between the two industries and identifies key factors that may promote positive interactions. Interactions between the two industries result from shared resource requirements (e.g., space, clean water, brood-stock, breeding programs), shared knowledge requirements (e.g. around threats and their mitigation, factors optimizing growth/survival) and biological interactions (e.g. over-catch, disease spill-over, competition for resources). Many of these interactions are reciprocated, and can shift from positive to negative depending on environmental, biological and socio-economic conditions. From our examination, three key factors emerge as shaping the strength and direction (positive or negative) of interactions: (1) whether the focal species is common or different between the two industries; (2) the physicochemical and socio-economic environment in which the two industries are occurring; and (3) whether there is open dialogue and consultation between the two industries and relevant stakeholders. Positive interactions can be maximized where the two industries are able to co-invest in and share infrastructure (e.g. hatcheries, breeding programs), resources (e.g. spat, broodstock, shell) and knowledge (e.g. optimal conditions of growth) – an easier task where the target oyster species is in common. Positive interactions may also be maximized by utilizing marine spatial planning tools, such as suitability modelling, to inform optimal siting of the two industries. As the two industries continue to grow, open and inclusive dialogue between these and key stakeholders will be essential for mitigating risk and maximising positive synergies.